Efficiency of fungicides against fungal potato rot - Andriychuk, T.; Skoreyko, A.; Mankovsky, M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The results of studies for determining fungicides efficiency against fungal potato rot during storage are presented. The post harvesting seed processing reduces the development of the disease from 18.8 to 6.4%, and the number of affected tubers decreases from 72 to 32%. The efficiency of the used preparations is 59.6—66.0%.